A small molecule that disrupts S. Typhimurium membrane voltage without cell lysis reduces bacterial colonization of mice - Dombach, Jamie L.; Quintana, Joaquin LJ; Allgood, Samual C.; Nagy, Toni A.; Gustafson, Daniel L.; Detweiler, Corrella S. (PLOS Pathogens, 2022)
Author summary As bacterial resistance to existing antibiotics increases and expands, scientists are exploring new approaches to combatting bacterial infections. There is a special need for antibiotics against Gram-negative bacteria, which are difficult to treat and can cause devastating infections. One underexplored possible antimicrobial target for Gram-negative bacteria is the bacterial cell membrane, a structure essential for viability. Here we describe a small molecule that inhibits a Gram-negative bacterial infection in host cells and mice. This molecule disturbs, but does not permeabilize, bacterial cell membranes under growth conditions that mimic infection. These data indicate that subtle bacterial membrane damage caused by a small molecule augments host innate immune defenses and enables bacterial killing, suggesting a new approach to antibacterial therapy.